TerraSAR-X/TanDEM-X sea state measurements using the XWAVE algorithm - Bruck, Miguel; Lehner, Susanne (International Journal of Remote Sensing, 2015)
The high-resolution TerraSAR-X (TS-X) satellite, which was successfully launched in 2007, and its twin TanDEM-X (TD-X), which was launched in 2010, deliver high-quality radar images over land and ocean, for scientific and commercial applications. We present an empirical algorithm, called XWAVE, to derive significant wave height ((Formula presented.)) from TS-X and TD-X data without the need for a priori information. A set of 200 TS-X/TD-X VV polarized StripMap synthetic aperture radar (SAR) images are collocated with in-situ measurements from buoys in water depths over 100 m. From that data set, 100 data pairs are used for tuning and the remaining 100 are taken for validation of the algorithm. The algorithm is based on Fourier analyses of TS-X/TD-X data and with coefficients which are fitted with collocated in situ buoy wave measurements. The algorithm takes into account the dependence of (Formula presented.) on incidence angle, sea surface wind speed, and wave propagation direction in relation to satellite heading. The validation results of (Formula presented.) derived by the XWAVE algorithm against in situ wave measurements show good agreement with a correlation coefficient, r, of 91%, a scatter index, Si, of 0.21, and a bias of 0.01 m. In addition, we also compare the wave peak period and peak direction derived from the SAR image spectra to those measured by buoys. Both comparisons showed good agreement, with verification results for peak period giving an r of 96% and Si of 0.13 and those for peak direction giving an r of 95% and Si of 0.14. Case studies are additionally shown for TS-X/TD-X acquisitions taken over different wave conditions and incidence angles, where the derived one-dimensional spectrum is compared graphically to the one derived from buoy data.
CRIS-Team Scopus Importer:2024-03-18